Narratives of time and gender in antiquity
1 online resource.
Keywords: "This volume offers new insights into ancient figurations of temporality by focusing on the relationship between gender and time across a range of genres. Each essay in this collection places gender at the center of its exploration of time, and the volume includes time in treatises, genealogical lists, calendars, prophetic literature, ritual practice, and historical and poetic narratives from the Greco-Roman world. Many of the essays begin with female characters, but all of them emphasize how and why time is an integral component of ancient categories of female and male. Relying on theorists who offer ways to explore the connections between time and gender encoded in narrative tropes, plots, pronouns, images, or metaphors, the contributors tease out how time and gender were intertwined in the symbolic register of Greek and Roman thought. Narratives of Time and Gender in Antiquity provides a rich and provocative theoretical analysis of time-and its relationship to gender-in ancient texts. It will be of interest to anyone working on time in the ancient world, or students of gender in antiquity"--